(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper presents a novel secure and efficient privacy-preserving data authentication scheme tailored for the Internet of Things (IoT) environment, addressing the growing concerns surrounding data security and user privacy in IoT applications. As the proliferation of IoT devices increases, so does the potential for unauthorized access and data breaches, necessitating robust authentication mechanisms that can safeguard sensitive information without compromising performance. Our proposed scheme leverages advanced cryptographic techniques to ensure secure data transmission while minimizing computational overhead, making it suitable for resource-constrained IoT devices. By employing privacy-preserving protocols, the scheme enables secure authentication without revealing sensitive user data, thus maintaining user confidentiality. Comprehensive evaluations demonstrate that our approach not only enhances security against various attack vectors but also optimizes efficiency in terms of processing time and energy consumption. This research contributes significantly to the ongoing efforts to develop secure IoT frameworks, facilitating a safer and more reliable IoT ecosystem while protecting user privacy.